2012
DOI: 10.1021/ic3018503
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Electronic Structure and Reactivity of One-Electron Oxidized Copper(II)-(Disalicylidene)diamine Complexes

Abstract: The neutral and one-electron oxidized Cu(II) six-membered chelate 1,3-Salcn (1,3-Salcn = N,N'-bis(3,5-di-tert-butylsalicylidene)-1,3-cyclohexanediamine) complexes have been investigated and compared with the five-membered chelate 1,2-Salcn (N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexane-(1R,2R)-diamine) complexes. Cyclic voltammetry of Cu(1,3-Salcn) showed two reversible redox waves at 0.48 and 0.68 V, which are only 0.03 V higher than those of Cu(1,2-Salcn). Reaction of Cu(1,3-Salcn) with 1 equiv of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
155
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(176 citation statements)
references
References 88 publications
21
155
0
Order By: Relevance
“…Complexes 1,2-salcn + , 1,3-salcn + , and saloph + showed similar reaction kinetics, suggesting that the reaction mechanisms are similar [87,92]. The kinetic isotope effect (KIE) with the use of α-d 2 -benzyl alcohol was estimated to be very large (k D /k H N 10), which indicates that hydrogen abstraction from α-position of the benzyl alcohol is involved in the rate determining step of the oxidation (Scheme 3) [95,96].…”
Section: One-electron Oxidized Aromatic Ring In Complexesmentioning
confidence: 89%
See 4 more Smart Citations
“…Complexes 1,2-salcn + , 1,3-salcn + , and saloph + showed similar reaction kinetics, suggesting that the reaction mechanisms are similar [87,92]. The kinetic isotope effect (KIE) with the use of α-d 2 -benzyl alcohol was estimated to be very large (k D /k H N 10), which indicates that hydrogen abstraction from α-position of the benzyl alcohol is involved in the rate determining step of the oxidation (Scheme 3) [95,96].…”
Section: One-electron Oxidized Aromatic Ring In Complexesmentioning
confidence: 89%
“…The resonance Raman spectrum of 1,3-salcn + exhibited a characteristic phenoxyl radical ν 7a Raman band at 1494 cm − 1 in CH 2 Cl 2 solution. From the results, 1,3-salcn + can be assigned to the Cu(II)-phenoxyl radical species with the radical electron localized on one of the two phenolate moieties both in the solid state and in solution [87]. On the other hand, the crystal structure of [Cu(4,5-diMeOsalophen)]SbF 6 (4,5-diMeO-saloph + ) (4,5-diMeOsalophen = N,N′-bis(3,5-di(tert-butyl)salicylidene)-1,2-diamino-4,5-dimethoxybenzene) showed that the counter anion is located at the proximal position of the 1,2-phenylenediamine moiety (Fig.…”
Section: One-electron Oxidized Aromatic Ring In Complexesmentioning
confidence: 97%
See 3 more Smart Citations